The new encyclopedia británica in 30 volumes. macropedia VOL.14 / William Benton - Benton, William (1977)
History, the contemporary city, general features, natural history, form function, classification, family , (tropic birds), family fregatidae (frigate brirds), the history of Pennsylvania, the natural and human landscape, the people of Pennsylvania, the state´s economy, administration and social conditions, cultural life and institutions, individual differences in perceiving, visual cues, form and function